Maternal exposure to intimate partner violence and breastfeeding practices of children 0-23 months: findings from the 2018 Nigeria Demographic and Health Survey - Tope Olubodun; Anteneh Asefa; Aduragbemi Banke-Thomas; Mobolanle Balogun; Ifeoma Okafor; Oluwakemi Odukoya; Lenka Beňová (Inishmore Laser Scientific Publishing Ltd, 2023)
# Background Intimate partner violence (IPV) is an important public health and human rights issue with high prevalence in Nigeria. Understanding the link between IPV and breastfeeding---an important intervention to reduce child morbidity and mortality---is critical and could inform strategies to promote breastfeeding and reduce IPV. This study examines the association between recent maternal experience of IPV and optimal breastfeeding of children aged 0 to 23 months in Nigeria. # Methods This secondary analysis of the 2018 Nigeria Demographic and Health Survey included a sample of 3,749 women aged 15 -- 49 years who had singleton live birth in the two years preceding the survey. The outcome variable was optimal breastfeeding for age (exclusive breastfeeding in the first six months of life and any breastfeeding from 6-23 months). We defined recent IPV as exposure to any IPV in the 12 months preceding the survey; we also included the number of forms of IPV experienced (0, 1, 2 or 3: physical, emotional, and sexual) as an additional categorical independent variable. We used frequencies and proportions to describe key variables. We then conducted two multivariable logistic regression models---with any IPV and number of forms of IPV to determine the crude and adjusted odds ratios between IPV and optimal breastfeeding for age. # Results Among all women, 31% experienced any IPV and 2.6% all three forms. Nearly one-third (31.7%) of babies \<6 months of age and 70.4% of 6--23-month-olds were optimally breastfed. We found no significant association between any IPV and optimal breastfeeding for age (adjusted odds ratio, aOR=0.92; 95% confidence interval, CI=0.76--1.14). However, women who experienced all three forms of IPV were significantly less likely to optimally breastfeed their children (aOR=0.58; 95% CI =0.36--0.93) than those with no IPV experience. # Conclusions Policies and strategies to promote breastfeeding should include measures to identify and mitigate IPV against pregnant and breastfeeding women and provide optimal psychological and breastfeeding support for those who are victims of IPV.